Analisis Sanad dan Matan Hadis tentang Musik - Pratiwi, Hanameyra (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss music in terms of hadith. This research method is a qualitative type through literature study with content analysis. The results and discussion of this study include general views about music, syarah hadith about music and hadith analysis about music. The conclusion of this study shows that there is a hadith that prohibits music, but that is if the music is done for a bad purpose. Music, which includes listening to music, playing musical instruments or singing, is permitted as long as it is not excessive or does not violate Islamic law prevailing in society, does not harm ourselves and others, and does not make us neglect or forget our obligations to Allah. swt. This study recommends to all Muslim audiences about the importance of knowing how the law of music in the perspective of hadith.